Sparse Closed-Loop Surface Related Multiple Elimination - Abdul Latiff, A.H. (Springer Science and Business Media Deutschland GmbH, 2022)
A new approach for multiple removal were developed using the closed-loop surface related multiple elimination (CL-SRME) method. Instead of directly updating the estimated primaries, the impulse response and the source wavelet are updated together during inversion as both are used to defines the primaries estimate. Through imposing the sparsity constraint toward the update of the primary impulse, the spiky primary impulse can be obtained and reduced the time for its convergence. Through example from both synthetic and field data of Malay Basin, it shows that this new approach works on both shallow and complex geological area. One advantage of using the new approach is it were able to recover the primaries continuity which are often missing due to primaries-multiples overlap. The faster rate of convergence also proves that this new approach could be an alternative to existing multiple elimination process such as SRME, EPSI or CL-SRME. Â© 2022, Institute of Technology PETRONAS Sdn Bhd.